Écrire et cartographier le nomadisme au XIXe siècle. L’exemple des Kalmouks - Virginie Tellier (Studia Romanica Posnaniensia, 2023)
This article proposes to reflect on the writing of nomadism by comparing three accounts of journeys made between 1797 and 1859 in Kalmyk territory: Voyage à Astrakan et au Caucase (Jan Potocki, 1797), Les Steppes de la mer Caspienne, le Caucase, la Crimée et la Russie méridionale (Xavier and Adèle Hom-maire de Hell, 1843-1845), Voyage au littoral de la mer Caspienne and The Volga (Moynet, 1860, 1867). The article first evocates the question of the place from which the visual, auditory and intellectual experience of the traveller is established; it then questions the distance, physical and symbolic, which separates the travellers from those they meet on the way; it finally attempts to relate the movement of the nomad, on the one hand, to the movement of the traveller, on the other.